A New Record of the Insect Defoliator, Pteroma plagiophleps Hamp. (Lepidoptera: Psychidae) from Mangroves along the Goa Coast (India) - Santhakumaran, L. N.; Remadevi, O. K.; Sivaramakrishnan, V. R. (Indian Forester, 1995)
No abstract